Dotawo: A Journal of Nubian Studies 4: Place Names and Place Naming in Nubia (Punctum Books, 2017)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and critical and theoretical approaches present in post-colonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of old kingdoms. Place names in Nubia have only received limited attention so far. The need for such a study guided the decision to dedicate the fourth volume of Dotawo to this very issue. Place names are by nature dynamic and may shift over the course of the centuries. Therefore, toponymy is particularly apt to diachronical studies and offer fertile ground for multi-disciplinary analysis. The contents of the volume embrace a wide time frame (from the beginning of recorded history until today) and consist of contributions from scholars active in all fields of Nubian Studies (philology, linguistics, history, archaeology, etc.). The goal has been to gather into one publication the fruits of the collaboration of specialists working with all sorts of theoretical and methodological tools on the successive periods of Nubian history with a focus on the names that identified the micro- and macro-localities where this history was taking place.